Le Commissaire Lamy rencontre le G20 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Le Commissaire européen au commerce, Pascal Lamy, a rencontré les...